Transição para a Idade Adulta e Adultez Emergente: Adaptação do Questionário de Marcadores da Adultez junto de Jovens Portugueses - Mendonça, Marina (2009)
This paper reports on the adaptation of the Questionnaire of Markers of Adulthood (Arnett, 2001) to a Portuguese sample. Inspired in the concept of Emerging Adulthood, psychological, biological, social and contextual transitional markers were measured by 37 items. By using data from a sample of Portuguese college students (N=224), validity evidence was provided by a five-dimensional structure of the questionnaire. Additionally, the results generally supported the hypothesized importance of psychological markers as key points in the definition of adulthood. Moreover, in the sub-samples of emergent adults who do not clear perceive themselves as adults’, financial independence was also valued as a key point for their self-definition of adulthood. This study contributes to current literature on emerging adulthood and offers a reliable and valid tool to measure the importance of transitional markers on the conceptualization of adulthood in Portugal.